Measurement of construction productivity in Singapore - Lo, Chee Khiong. (2009)
This dissertation describes a study which has tested and developed productivity indicators for productivity measurement for Public and Private Residential projects. A survey was carried out on six on-going Residential projects for a period of 15 months. The results revealed the productivity performance of each of the Residential projects, and also showed its effectiveness and usefulness for comparing productivity among projects.